Can the 6-minute walking test evaluate all patients with respiratory disease? - Pimentel, Marta R. Q.; Raphael, Yves; Nascimento, Luciane V. B.; Rufino, Rogério; Maiworm, Adalgisa; da Silva, Kenia Maynard; da Costa, Cláudia Henrique (Brazilian Journal of Health and Biomedical Sciences, 2019)
The 6-minute walking test (6MWT) is a submaximal test used as a clinical indicator of functional capacity in patients with pulmonary disease. However, is has not been defined whether the parameters obtained in the 6MWT are similar in two groups of interstitial lung diseases (ILD), systemic sclerosis (SSc) and idiopathic pulmonary fibrosis (IPF), and what are the differences when compared to patients with chronic obstructive pulmonary disease (COPD). This is a comparative cross-sectional study of 6MWT data, with the inclusion of 32 patients with SSc, 32 with IPF and 50 with COPD. All patients underwent the 6MWT and a respiratory function test. Patients with ILD did not present significant differences when compared with each other. However, when compared to patients with COPD, the ILD group showed greater distance walked (ILD = 404.6 ± 1.09m, COPD = 352.4 ± 10.80m; p = 0.0033) and predicted percentage above 100% (ILD = 113.5 ± 3.72%, COPD = 84.36 ± 4.81%; p <0.0001). Both groups showed a drop in blood oxygen saturation (SaO2) at the end of the test, but the difference between the measured values before and after the 6MWT was more significant in the ILD group (ILD = 10.33 ± 01.09%, COPD = 4.60 ± 12.37%; p <0.0001). The data suggest that, differently from COPD patients, the main parameter to be evaluated during the 6MWT in the ILD group could be the drop in saturation and not the distance walked. Keywords: COPD; Lung diseases, Interstitial; Respiratory Function Tests; Walk Test; Walking.